Methodology Of Teaching The Topic Of Rational Inequalities In School Mathematics Courses - Juraeva Nargiza Oltinboyevna; Safarova Nigora Nasulloyevna (Genius Publishing Group, 2025)
The main goal of this work is to develop effective methods for teaching the topic of rational inequalities in school mathematics courses and to demonstrate their practical application. Rational inequalities are an important part of the algebra course, and mastering them helps develop students' mathematical thinking abilities. The article discusses the definition, types, and basic methods of solving rational inequalities, as well as the difficulties encountered in solving them and ways to overcome these difficulties.
Keywords: rational inequalities; teaching methodology; algebra